Why K. M. Metcalfe (Mrs Chapman) is 'Really the Originator in the Editing of Jane Austen'. (16th February 2017) - Barchas, Janine
Abstract: This article adjusts the prevailing origin story of Jane Austen studies. K. M. Metcalfe's edition of Pride and Prejudice, published in 1912 by Oxford University Press, has not had its due as the modern landmark 'first' that it was. Instead, the legacy of R. W. Chapman has been allowed to usurp the accomplishments of Katharine Marion Metcalfe (1887–1978), a pioneering editor who was the first fully to rescue Austen's text from a near-century of careless reprintings—eleven years before Chapman's important 1923 edition of Austen's works, which mimics Metcalfe's volume in virtually every detail. The fact that Katharine Metcalfe became, in 1913, Mrs R. W. Chapman and allowed her husband to take over the project that she had begun should no longer mask her role as, in her own words, 'really the originator in the editing of Jane Austen'. This article newly traces the step-by-step genesis of Metcalfe's ground-breaking edition.